Social spaces for young children in hospital. Issue 2 (7th January 2013) - Lambert, V.; Coad, J.; Hicks, P.; Glacken, M.
Abstract Background In the last number of years heightened interest has been attributed to the impact of hospital environments on children's psychosocial well‐being. With policy largely built around adult assumptions, knowledge about what constitutes a child‐friendly hospital environment from young children's perspectives has been lacking. If hospital environments are to aspire to being child friendly then the views of younger aged children must be taken into account. The current study investigated young children's perspectives of hospital social spaces to inform the design of the built environment of a new children's hospital. Methods An exploratory qualitative participatory design was employed. Data were collected through semi‐structured interviews (one‐to‐one and group workshops) which incorporated art‐based activities to actively engage young children. Fifty‐five young children aged 5 to 8 years with various acute and chronic illnesses were recruited from inpatient, outpatient and emergency departments of three children's hospitals. Results Young children want a diversity of readily available, independently accessible, age, gender and developmentally appropriate leisure and entertainment facilities seamlessly integrated throughout the hospital environment. Such activities were invaluable for creating a positive hospital experience for children by combating boredom, enriching choice and control and reducing a sense of isolation through enhanced socialization. When in hospital, young children want to feel socially connected to the internal hospital community as well as to the outside world. Technology can assist to broaden the spectrum of children's social connectivity when in hospital – to home, school and the wider outside world. Conclusion While technology offers many opportunities to support children's psychosocial well‐being when in confined healthcare spaces, the implementation and operation of such services and systems require much further research in the areas of ethics, facilitation, organizational impact and evaluation.